Designing an Artificial Agent for Cognitive Apprenticeship Learning of Elevator Pitch in Virtual Reality - Zhao, Zhenjie; Ma, Xiaojuan (IEEE transactions on cognitive and developmental systems, 2022)
Developing social skills like elevator pitch requires being situated within authentic activities and contexts, which is difficult to achieve on a daily basis. In this work, we explore whether an artificial agent with embodied feedback in virtual reality (VR) can foster a situated learning experience. Previous works on computer-mediated feedback have shown that VR can foster oral presentation competence for preuniversity and junior undergraduates through delivering feedback. However, it is unclear how well the learning experiences are and how well students perceive an artificial coach in VR, especially for senior undergraduates and postgraduates seeking job and research opportunities. To inform the design of such a system, we conducted interviews with experts and observed real elevator pitches. We then designed a proof-of-concept VR coaching system with three embodied feedback strategies: immediate, after-action, and the combination of both. Through a between-subject experiment with 40 participants, we studied learners' perceptions under the embodied feedback. We found that receiving embodied feedback can create a stronger sense of cognitive apprenticeship, i.e., coaching and helping from experts, and help improve the perception of the artificial agent and the effect of learning. We further investigated the pros and cons of different strategies and discussed room for improvement.